Approche de la capacité trophique dans le bassin ostréicole (Baie de Bourgneuf) - Haure, Joel; Baud, Jean-pierre (1995)
A hydrobiological study coupled with the evolution of the production of cupped oysters Crassostrea gigas has been carried out from March 1990 to March 1991 on two oyster culture areas (North and South) of the Bay of Bourgneuf. - The northern area is characterized by an environment which is variable though time and composed of a high nutritive and mineral load. This high particular load (average value = 154 mg.l- 1) is linked to meteorological conditions and especially to the wind speed and direction. The individual growth of cultivated oysters is low (i.e.: 58.8 g). - The southern area shows homogenous hydrobiological characteristics throughout the year. The average phytoplanktonic biomass is 4.4 µg.l-l of chlorophyll and the particular load is low (average value = 34 mg.l- 1). In this case, the individual growth of cultivated oysters is higher, (i.e.: 67.2 g). The study of the oyster/environment relationship in the Bay of Bourgneuf showed that oysters' growth seems more correlated to the quality of the food ("mineral matter/total matter" ratio) than to the total available quantity. This tendency could be the consequence, in the presence of a high particular load, of a "dilution" of the food by the mineral part of the suspended matter and of the activation of the "sorting" function, which is energy consuming in the cupped oyster. .Une étude hydrobiologique couplée à l'évolution de la production d'huîtres creuses Crassostrea gigas a été menée de mars 1990 à mars 1991 sur deux secteurs ostréicoles (Nord et Sud), de la baie de Bourgneuf. - Le secteur nord est caractérisé par un milieu variable au cours du temps composé à la fois d'une charge nutritive et minérale élevée. Cette forte charge particulaire (valeur moyenne = 154 mg.l- 1) est liée aux conditions météorologiques et plus particulièrement à la direction et à la vitesse du vent. La croissance individuelle des huîtres en élevage est faible, (i.e: 58,8g). - Le secteur sud possède des caractéristiques hydrobiologiques homogènes au cours de l'année. La ...